New routes for synthesis of azole and/or azine derivatives utilizing hydrazones as starting materials - Rasha Ibrahim Elsholkamy; Abdelatif Mohamed Salah Eldine; Ebtisam Abdelaziz Hafez (Cairo : Rasha Ibrahim Elsholkamy, 2008)
Azaenamines derivatives react with a, B -unsaturated nitriles to yield dihydroaminopyridazines on the other hand reaction of azaenamines with mixturee of benzaldehyde and malononitrile gave the crotononitrile derivative
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Organic Chemistry
Issued also as CD
Keywords: Azaenamine; Pyridazine; Pyridazineone